TRANSFORMASI PEMBELAJARAN BERBASIS PROYEK SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS DI MASA PANDEMI COVID-19 - Saputra, Beny; Sujarwanta, Agus (Universitas Muhammadiyah Metro, 2021)
This research focuses on the transformation of project-based learning (PjBL) Science, Technology, Engineering, and Mathematics (STEM) during the Covid-19 pandemic, where learning in schools experienced a significant change from conventional learning (face-to-face) to online learning, follow the health protocol physical distancing recommended by the current government. STEM-PjBL online learning through platform was e-learning effectively carried out during the Covid-19 pandemic by providing projects to students involving science, technology, engineering and mathematics. STEM-PJBL learning enhances learning outcomes, learners' competencies and learning motivations, creates more meaningful learning, helps students solve problems, and supports future careers. The use of online applications for learning in the form of google classroom and social media becomes the main choice based on the level of ease of use. STEM-PJBL. This STEM-PjBL learning also demonstrates students' scientific abilities including reading, observing, and solving problems in daily life. The improvement of life skills includes personal, social, academic and vocational skills. This integration is more effective than conventional learning in improving learning outcomes in the form of creative thinking skills and science process skills. The constraints of online learning include limited internet services, as well as user infrastructure and infrastructure, some of which have not yet been fulfilled, for example smartphones and laptops, so that further and maximum efforts are needed from all parties.